Environmental Facility of Food Products as a Factor of Market Positioning - Kozak, Liudmyla; Kostetska, Iryna; Bereziak, Ivanna (Studia Ecologiae et Bioethicae, 2024)
The purpose of the article is to analyze the reactions of consumers to the quality characteristics of food products, in particular related to the level of their environmental friendliness, in order to develop proposals for improving the communication programs of manufacturers of these products in Ukraine. The authors describe the reactions of consumers to the qualitative characteristics of food products based on the results of a sociological study. 1269 people participated in the study, including 539 (42.5%) men and 730 (57.5%) women. The distribution of respondents by age is as follows: from 18 to 20 years old - 68 people or 5.4%; from 21 to 30 years old - 367 people or 28.9%; from 31 to 40 years old - 705 people or 55.5%; over 40 years old – 129 people or 10.2%. The age structure of respondents shows that about 90% of respondents belong to generations Y and Z, according to the well-known American classification. The intensifying competition among food manufacturers in Ukraine requires them to improve their own communication programs and positioning strategies by identifying significant emotional and functional attributes of the specified products. The conducted sociological study of the purchasing behavior of consumers on the food market in Ukraine contributes to the solution of this problem. The authors identified a number of factors influencing the formation of stereotypes of food quality perception. Indicators of environmental friendliness and safety for human health turned out to be the most important attributes in market positioning. The results of the study serve as a methodological basis for improving the communication programs of food manufacturers, contribute to the development of healthy competition among them. The findings of this study can be considered important as a guide for future research.